Development of a surgical technique for partial cortico-hippocampectomy and standardized histologic evaluation of the hippocampal cytoarchitecture in normal cats - Zilli, Jessica; Justus Liebig University Giessen (My University, 2022)
Cats, like humans, are known to be affected by hippocampal sclerosis (HS), potentially causing antiepileptic drug (AED) resistance. In humans, temporal lobe resection is a standardized therapy in patients with refractory temporal lobe epilepsy (TLE). Therefore, the purpose of this prospective cadaveric study is to establish a surgical technique for hippocampal resection in cats as a treatment for AED resistant temporal seizures and to define normal reference values on cellular density and cytoarchitecture for the different parts of the feline hippocampus, which is a necessary premise for a standardized examination of post-surgical hippocampal specimens. First, ten cats of different head morphology were examined. A pre-surgical 3D reconstruction of the head, brain, and hippocampus was obtained. Post-operatively, an MRI scan of the brains as well as a histological examination of the resected hippocampal specimens and the brains were performed to assess the presence of tissue injury adjacent to the surgical site and the completeness of the resection. The feasibility of the established surgical procedure, as well as the usability of the removed specimens for histopathological examination was assessed. In all cats but one, the resection of the temporal cortex and the hippocampus was successful. In one cat, the presence of tissue damage in the thalamus was suspected in the histopathologic examination of the brain post-resection; however, the postsurgical brain MRI of the same cat was unremarkable. All hippocampal fields and the granule cell layer (GCL) were identified in five cats via histological examination. The second part of the study focused on the evaluation of the hippocampal pyramidal cell layer cytoarchitecture; in particular, all CA areas and the GCL of the dentate gyrus (DG), which are known to undergo profound structural changes in cases of HS, were assessed. Three transverse sections (head, body and tail) of each left hippocampus were obtained from 17 non-epileptic cats of different brachycephalic and mesocephalic breeds and age classes. Histological (H&E, Nissl) and immunohistochemical (NeuN, GFAP) staining were performed to investigate neuronal and astroglial cell populations, and layer thickness (LT) of the pyramidal cell layer and GCL. Significant differences in neuronal density (ND) and LT could be evidenced throughout the longitudinal hippocampal axis (p < 0.05); on the other hand, the astrocyte densities (AD) did not differ except in CA1 and in the GCL. Moreover, reference ranges for these parameters were defined. The factors breed and age did not influence ND, AD or LT. The study describes a new surgical approach offering a treatment for cats with AED resistant TLE, which may become a therapy option for these animals. Moreover, estimating normal values of the hippocampal cytoarchitecture will help in the standardized histopathological examination of resected hippocampal specimens to reach a diagnosis of HS.
Keywords: TLE; cat; epilepsy; surgery; hippocampus; cytoarchitecture; temporal; ddc:610